ChemInform Abstract: Luminescent Chemosensors Based on Silica Nanoparticles for the Detection of Ionic Species. Issue 17 (4th April 2013) - Montalti, Marco; Rampazzo, Enrico; Zaccheroni, Nelsi; Prodi, Luca
Abstract Review: 43 refs.